An Analysis of AMPK and Ferroptosis in Cancer: A Potential Regulatory Axis - Ting Zhang; Xi Wang; Peter G Alexander; Peng Feng; Jianying Zhang (Frontiers in Bioscience-Landmark)
Adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) is an energy homeostasis controller that regulates various metabolic pathways to promote adenosine triphosphate (ATP) generation and suppress energy expenditure, thereby restoring energy homeostasis. As a co-factor in many enzymes, iron is an essential mineral for maintaining ATP levels in our bodies. Ferroptosis is an iron-dependent mode of cell death that occurs in various pathological processes, including cancer, metabolic disorders, and autoimmune diseases, by regulating iron metabolism, lipoperoxidation, and anti-oxidation functions. Ferroptosis is triggered by oxidative and energy stress, both controlled by cancer-associated signaling pathways. Emerging studies have demonstrated that AMPK directly influences ferroptosis by modulating lipid metabolism, redox homeostasis, and iron transport. Cancer cells exhibiting elevated baseline AMPK activity demonstrate resistance to ferroptosis, whereas AMPK suppression enhances their susceptibility to this regulated form of cell death. While the precise mechanistic details are yet to be fully elucidated, accumulating evidence suggests that AMPK-mediated ferroptosis regulation may contribute to cancer development and therapeutic responses. This review summarizes recent advances in understanding the interplay between AMPK and ferroptosis in cancer biology and discusses the potential of targeting the AMPK-ferroptosis axis for innovative anticancer strategies.